Peran Lembaga Pendidikan Sekkau Dalam Menyiapkan Peserta Didik Profesional Di Era Society 5.0 - Hanny Sahupala; Jimmy Venny Tokio Tiwow; Linda Sartika; Agus Pudjianto (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
The role of the Sekkau educational institution is to prepare various things that are included in the education component such as the readiness of educational facilities, the readiness to develop the existing curriculum, the readiness of human resource providers (HR), alins/alongin with a perspective on society 5.0, by improving the quality of student outcomes. superior ones who have future insights equipped with various developments such as the quality of human resources, curriculum development, and equipped with competency standards and innovations for lecturers to be able to improve the quality of students in educational learning. Furthermore, it produces several developments in the form of educational goals in line with educational goals and strategies that have been planned by carrying out various evaluations which include involving educational facilities (fasdik), girls (education staff), curriculum development and the condition of students who can attend education with psychological and mental qualities. physically healthy and able to understand every lesson provided by the institution. The Lecturer profession also makes changes both in analysis and application as well as innovations that can increase changes towards technological progress.